2023
DOI: 10.1002/mrm.29803
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time fetal brain tracking for functional fetal MRI

Abstract: PurposeTo improve motion robustness of functional fetal MRI scans by developing an intrinsic real‐time motion correction method. MRI provides an ideal tool to characterize fetal brain development and growth. It is, however, a relatively slow imaging technique and therefore extremely susceptible to subject motion, particularly in functional MRI experiments acquiring multiple Echo‐Planar‐Imaging‐based repetitions, for example, diffusion MRI or blood‐oxygen‐level‐dependency MRI.MethodsA 3D UNet was trained on 125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…One of the possible solutions could be based on more advanced integration of the reconstruction code into the Gadgetron interface: e.g. dynamic masking, reorientation 21 and sequential addition of stacks to the reconstruction function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the possible solutions could be based on more advanced integration of the reconstruction code into the Gadgetron interface: e.g. dynamic masking, reorientation 21 and sequential addition of stacks to the reconstruction function.…”
Section: Discussionmentioning
confidence: 99%
“…Several fetal MRI research works reported scanner-based solutions for real-time brain tracking 21 and automated detection and re-acquisition of low-quality slices 22 . Both solutions implemented interaction between the scanner and external GPU-accelerated research reconstruction workstations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A bounding box encompassing the fetal brain is calculated and used for the following landmark detection task. 18…”
Section: Localization Of the Fetal Brainmentioning
confidence: 99%
“…Specifically in fetal MRI, work showed the ability to perform quality control, 14 automatic segmentation, 15,16 and automatic tracking. 17,18 Automatic field-of-view prescription was shown in the abdomen using deep learning segmentations 19 and in the heart using tracking based on landmarks 20 with successful detection ratings of 99.7%-100% for cine images and Euclidean distances between manual and automatically detected labels from 2 to 3.5 mm. Similar work in the brain detecting landmarks such as the anterior and posterior commissures and subsequently the symmetry line using multitask deep neural networks were demonstrated among others by Yang et al 21 Specifically for fetal MRI, segmentation of the eye region and detection of the general head position was suggested by Hoffmann et al 22 using classical image processing methods such as maximally stable extremal regions and by Xu et al 23 using convolutional networks-both applicable for real-time slice planning in the future.…”
Section: Introductionmentioning
confidence: 99%